Fulfillment of homosexual desires as a radical action in bethan roberts' novel my policeman: Slavoj Žižek's perspective - Faradilla, Dhitya; Marnani, Niken Indah (Gema Wiralodra, 2023)
The purpose of this study is to reveal the subjectivity of the character Tom in the novel My Policeman in fighting symbolic norms to fulfill his desires as a homosexual. Based on these objectives, interesting researchers In conducting this research researchers used the novel My Policeman, in the analysis will focus on the main character, namely Tom who is a homosexual. The purpose of this research is to reveal the subjectivity of the character Tom in the novel My Policeman in fighting the symbolic order to fulfill his desires as a homosexual. In explaining the subjectivity of the characters, the subject theory proposed by Slavoj Žižek is used. The method used in conducting this research is a qualitative descriptive method. The results of the study show that Tom's actions to follow his desire to enter into same-sex relationships make him classified as homosexual and ignore the sanctions he will receive, as a form of cynical subject. Tom fights against the symbolic dimension as a form of radical action by having same-sex relationships or being a homosexual. The radical action taken by Tom is a form of fulfilling the desire that is in him to achieve freedom. The freedom that kept him together with Patrick was due to a different kind of sexual urge that arose within Tom. Tom fights against the symbolic dimension as a form of radical action by having same-sex relationships or being a homosexual. The radical action taken by Tom is a form of fulfilling the desire that is in him to achieve freedom. The freedom that kept him together with Patrick was due to a different kind of sexual urge that arose within Tom. Tom fights against the symbolic dimension as a form of radical action by having same-sex relationships or being a homosexual. The radical action taken by Tom is a form of fulfilling the desire that is in him to achieve freedom. The freedom that kept him together with Patrick was due to a different kind of sexual urge that arose within Tom.